Study on the effect of protein on drug efficacy: cefonicid sodium–pepsin binding mechanism. Issue 5 (28th May 2019) - Liu, Bao-Sheng; Ma, Li-Hua; Bian, Gang; Wang, Chun-Dan; Zhang, Hong-Cai; Cheng, Xu
Abstract: The mechanism of interaction between cefonicid sodium and pepsin was investigated by various spectroscopic methods and molecular docking. Cefoncid sodium quenched the intrinsic fluorescence of pepsin at pH of 2.0 to form a new complex in a 1:1 binding mode driven by Van der Waals and hydrogen bonds. The mechanism of quenching was static. The results of molecular docking indicated that the cefonicid sodium-binding site was located in the active site of pepsin. The protein binding rates of cefonicid sodium in gastric juice was calculated and the binding model was established. It is concluded that cefonicid sodium is not suitable for oral administration.